A review of the Stelidium group of Stelis Panzer, 1806 (Hymenoptera: Megachilidae) with two new species from western North America - Sheffield, Cory S. (Zootaxa, 2024)
The Stelidium group is readily distinguished from all other members of the subgenus Stelis Panzer, 1806 by the combination of small body size (≤ 6 mm), pale maculations on the head adjacent to the inner margins of the compound eyes and laterally on the vertex in both sexes, and females with sternum 6 extended beyond tergum 6, the former with the dorsal lip trowel-shaped with the apex broadly rounded or subtruncate to more narrowly pointed. This monophyletic clade, which is endemic to North America, currently consists of members previously placed into two species groups: the permaculata group containing S. anasazi Parker & Griswold, 2013, S. ashmeadiellae Timberlake, 1941, S. permaculata Cockerell, 1898, and S. robertsoni Timberlake, 1941, and the palmarum group containing S. broemelingi Parker & Griswold, 2013, S. elongativentris Parker, 1987, and S. palmarum Timberlake, 1941; two additional species, S. herberti (Cockerell, 1916) from Mexico, and S. nyssonoides (Brues, 1903) from Texas, United States, have not been definitively placed in either species group. Two new species are herein described, one from southcentral British Columbia, Canada, the other from New Mexico, United States. A preliminary molecular phylogeny places both new species in the permaculata species group. In addition, S. herberti is also placed within the permaculata species group based on morphological similarity, sharing the multi-spotted maculation pattern on the terga. Based on molecular affinity, S. broemelingi also belongs to the permaculata species group. Because no type specimen for S. nyssonoides is seemingly available for examination, it is hereby considered nomen dubium until the specimen is found and its taxonomic status clarified in relation to the more recently described species in the permaculata species group. A key to females and diagnoses are provided for all known taxa.